Recurrent noncoding U1 snRNA mutations drive cryptic splicing in SHH medulloblastoma - Suzuki, Hiromichi; Kumar, Sachin; Pfister, Stefan (Nature, 2019)
Highly recurrent hotspot r.3A>G mutations are identified in U1 splicesomal small nuclear RNAs in about 50% of Sonic hedgehog medulloblastomas, which result in disrupted RNA splicing and the activation of oncogenes.